V-Type solar still integrated with hybrid solar concentrator. Issue 1 (31st December 2022) - Kiran, A. Amrith; Sivashankar, P. Veena; Suneesh, P.U.; Denkenberger, D.C.
Abstract: In this paper, the experimental performance of a "V" type solar still coupled with a hybrid solar concentrator (HSC) and Heat exchanger (HX) are presented. A high yield, inexpensive solar desalination system is constructed almost entirely from salvaged components. Even though it requires a mild maintenance, the necessary skills of operation are rudimentary and the cost of maintenance is low. The HSC focuses the solar radiation to a particular area and it offers a higher concentration ratio than conventional linear focus types. The HX is placed on the focus of the HSC and is connected to the basin of the "V" type solar still. A higher basin water temperature will be achieved by the "V" type solar still due to the additional heat from the HX, causing the brackish water to evaporate leaving behind all the contaminants. When comparing the performance analysis of "V" type solar still to that of the same still incorporated with the HSC, the efficiency of the latter improved from 20% to 36%, the amount of distillate production per unit area increased 4.17 kg/m 2 to 7.42 kg/m 2 and the latter also experienced an 80% more total distillate productivity. The cost per liter of the distillate was also found to be 0.0027 $/ which is significantly cheaper than that from other conventional solar stills.